Student Teams Achievement Division (STAD) Learning Model Assisted by Whole Number Puzzle Media to Enhance Mathematical Knowledge Competence - Luh Ayu Trishna Savitri; Gusti Ngurah Sastra Agustika; Anak Agung Ayu Dewi Sutyaningsih (Mimbar Ilmu, 2025)
Mathematics learning in elementary schools is often considered difficult and less engaging, particularly in the topic of whole numbers, which affects students’ knowledge competence. This study aims to examine the effect of the Student Teams Achievement Division (STAD) learning model assisted by whole number puzzle media on the mathematical knowledge competence of third-grade students. This research employs a quantitative approach with an experimental design, specifically a quasi-experimental design. The experimental design used is the Non-Equivalent Control-Group Design. The population of this study consisted of all third-grade classes in one cluster, totaling 195 students. The sampling technique used was cluster random sampling. The sample comprised third-grade students from two schools, divided into control and experimental groups. The data collection method and instrument used were mathematics knowledge competence tests. Data were analyzed using descriptive and inferential statistical techniques. The results indicated that students who learned using the STAD model assisted by puzzle media achieved significantly higher learning outcomes compared to students who received conventional instruction. The implication of this study highlights the importance of employing engaging learning models to enhance student involvement in elementary schools.